The influence of non-verbal educational and therapeutic Practices in autism spectrum disorder: the possibilities for physical education professionals - Campelo de Lima, Adryelle Fabiane (2017)
The individual with autism spectrum disorder (ASD) have symptoms that begin in childhood and affects the individual's ability to function in life and in their day to day. For reduce and control the symptoms of ASD exist several types of practices. Thus, this study aims to analyze the contributions of the main pedagogical and therapeutic practices of non-verbal communication in motivation, emotional stability, communication and socialization of individuals with autism spectrum disorders, which may collaborate in the intervention of the physical education professional. The study was done through a systematic review that was conducted in the electronic databases. Initially, 390 documents have been identified. After the reading and analysis of the titles of the documents, have selected 109. After reading the summaries were considered eligible 53 and, finally, we've included 18, which completely satisfy our criteria for inclusion. The results showed that intervention programs are distinct and the majority is in music therapy. This systematic review showed that there is direct intervention of physical education professionals only in psychomotricity.